2013
DOI: 10.1177/0956462413515193
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial correlates of HIV testing among men who have sex with men in Italy: a cross-sectional study

Abstract: The objective of this study was to understand the psychosocial correlates of men having sex with men (MSM) who have never been tested (never testers), MSM who have been tested in the last 12 months (recent testers), and MSM who have been tested before (remote testers). A sample of 14,409 Italian HIV-negative adult MSM was recruited via instant messages to the members of five international commercial websites and through clickable banner advertisements on different websites. The most important correlates of nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…Finally, being diagnosed with one or more STI was also associated with being diagnosed with HIV and decreased the chance that MSM had never been tested for HIV. These factors are largely in line with previous studies using EMIS data [ 18 , 19 , 24 ]. In addition, being tested for HIV (and especially being tested positive) increased the risk of being diagnosed with STI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, being diagnosed with one or more STI was also associated with being diagnosed with HIV and decreased the chance that MSM had never been tested for HIV. These factors are largely in line with previous studies using EMIS data [ 18 , 19 , 24 ]. In addition, being tested for HIV (and especially being tested positive) increased the risk of being diagnosed with STI.…”
Section: Discussionsupporting
confidence: 91%
“…In the future, we plan to compare additional variables of EMIS and SMON, which were omitted in the current study because they were unavailable in SOAP. It will be possible to look at other psychosocial factors, such as unsafe anal intercourse with steady and casual partners, knowledge, and beliefs [ 18 , 19 , 24 ]. Besides limitations of overlap between the databases, strengths of this research are in the sample sizes of all three databases.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies [ 31 , 43 ] (both with MSM) measured perceived behavioural control and found significant independent associations with previous testing. One study found a large independent effect of the related construct of testing self-efficacy on testing [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies measured internalised homophobia. One [ 49 ] found a significant negative association with previous testing, two failed to show an effect [ 66 , 98 ]. One study [ 66 ] also measured openness of homosexuality and found a significant positive association with previous testing.…”
Section: Resultsmentioning
confidence: 99%
“…However, testing rates in MSM are far from fulfilling the current European Centre for Disease Prevention and Control (ECDC) recommendation of testing at least once every 12 months [9] and studies describe a substantial percentage of MSM that have never even been tested for HIV [10][11][12][13][14][15]. Historically, the primary model for providing HIV testing has been client-initiated HIV testing (CIT) in which individuals must actively seek an HIV test at a health or community-based facility.…”
Section: Introductionmentioning
confidence: 99%